Economic analysis for the transport and storage of captured carbon dioxide in South Korea. Issue 3 (10th September 2013) - Zahid, Umer; Lee, Ung; An, Jinjoo; Lim, Youngsub; Han, Chonghun
<x xml:space="preserve">Abstract</x> The continuous rise of CO2 emissions is a major cause of global climate change. Carbon capture and storage (CCS) is widely seen as a practical technology for reducing CO2 emissions. CCS mainly consists of capturing CO2 from large emitting sources and its transportation to a sequestration site where it can be stored safely for a long period of time. The average CO2 emission growth rate of Korea is 1.0% which is the second highest among the Organization for Economic Co‐operation and Development (OECD) countries. It becomes even more challenging when CO2 is transported to an offshore storage since there is little experience with subsea pipelines for CO2 transportation. In this study, a plausible transport and storage model scheme has been developed and then employed to study different offshore CO2 transportation cases for South Korea as: CO2 transport in liquid phase (Temperature= −20°C, Pressure= 6.50 MPa); CO2 transport in liquid phase (Temperature= 5°C, Pressure= 9.30 MPa); CO2 transport in supercritical phase (Temperature= 40°C, Pressure= 15.00 MPa). CO2 storage capacity in sedimentary basins of Korea is evaluated between 19 and 27.2 Gt (giga‐ton) of CO2. Finally, this paper explores the costs associated with transport and geologic sequestration of CO2. Transport cost varies from 10.9 to 15.5 US$/tCO2 while the storage cost ranges from 20.8 to 21.3 US$/tCO2 depending on the specific scenario and depth at which CO2 is stored. Sensitivity analysis showed a decrease in storage cost of 62.4% and 93.6% in 2030 and 2050 respectively for projected CO2 volumes in Korea. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 978–992, 2014